Impact of Distribution of Costs and Benefits of Non-Reform Case Study of Power Sector Reforms in Kerala between 1996 and 2000 - V SANTHAKUMAR (Economic and Political Weekly January 11, 2003, 2003)
This paper studies the power sector reforms initiated by the Left Front government in Kerala between 1996-2000, which was aimed mainly at enhancing generation capacity and improving the efficiency of the state electricity board. It looks at the potential gainers and losers of the two components of the reform policy. The study provides a broad indication of the kind of distribution of costs and benefits of non-reform that would be conducive to sustaining reforms, especially with support from the electorally influential middle class.